Understanding Underexplored Communication Challenges: Lived Experiences of Caucasian Expatriates in Jakarta’s Corporate Sector: A Constructivist Grounded Theory Study in Jakarta’s Corporate Sector - Kersten, Tim; Poespodihardjo, Ari S. Widodo (Jurnal Spektrum Komunikasi, 2025)
This article explores the underexplored communication challenges experienced by Caucasian expatriates working in Jakarta’s corporate sector. In this business sector in Jakarta there are many significant intercultural communication challenges that take place for Caucasian expatriates that need to be addressed. Therefore, this study investigates how Caucasian expatriates deal with underexplored communication challenges such as stereotypes, different communication styles, language barriers, religious customs, workplace misunderstandings, and also Orientalist perceptions. These communicative dynamics are analyzed in relation to their impact on Caucasian expatriates’ adaptation, psychological well-being, and workplace productivity. To examine these issues, the research uses a qualitative approach utilizing in-depth interviews to gather data from Caucasian expatriates who have experience working in Jakarta's corporate sector. The data were analyzed using the grounded theory that allows for the emergence of key themes and patterns in challenges related to communication and adaptive strategies. The findings from the data reveal frequent misinterpretations, unclear expectations, and cultural communication norms that hinder smooth workplace interaction. Based on the results, this research proposes practical strategies to improve aspects such as communication, intercultural awareness, and professional integration for Caucasian expatriates. Additionally, it offers recommendations for companies in Jakarta's corporate sector to promote more inclusive environments. By providing actionable insights, this article contributes to a more nuanced understanding of intercultural communication issues and supports the development of more effective communication practices in Jakarta’s corporate sector.